Verifying nomenclature of DNA variants in submitted manuscripts: Guidance for journals. Issue 1 (10th December 2020) - Higgins, Jan; Dalgleish, Raymond; den Dunnen, Johan T.; Barsh, Greg; Freeman, Peter J.; Cooper, David N.; Cullinan, Sara; Davies, Kay E.; Dorkins, Huw; Gong, Li; Imoto, Issei; Klein, Teri E.; et al.
Abstract: Documenting variation in our genomes is important for research and clinical care. Accuracy in the description of DNA variants is therefore essential. To address this issue, the Human Variome Project convened a committee to evaluate the feasibility of requiring authors to verify that all variants submitted for publication complied with a widely accepted standard for description. After a pilot study of two journals, the committee agreed that requiring authors to verify that variants complied with Human Genome Variation Society nomenclature is a reasonable step toward standardizing the worldwide inventory of human variation.